2018
DOI: 10.1155/2018/9210490
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1/Foxo Axis Plays a Crucial Role in the Mechanisms of Therapeutic Effects of Erzhi Pill in Ovariectomized Rats

Abstract: Background. Erzhi pill (EZP), a traditional Chinese herbal formula, has been widely used to treat postmenopausal osteoporosis (PMOP) in China. However, its molecular mechanisms remain unclear. The aim of the present study is to investigate the antiosteoporotic effect of EZP on an ovariectomized rat model of PMOP. We performed the biomarkers of bone metabolism disorder, bone morphology, bone mineral density (BMD), and bone biomechanics to confirm the successful establishment of the PMOP model. We then investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…At the same time, Liang W et al claimed that the SIRT1/FoxO3a axis is a potential target for osteoporosis treatment, which suggests that the SIRT1/FoxO3a contributes to orthopedic diseases [ 41 ]. Consistent with the above research, this article revealed that miR-30b-5p bound to SIRT1 and repressed its expression, and overexpressing miR-30b-5p inactivated SIRT1 and FoxO3a.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, Liang W et al claimed that the SIRT1/FoxO3a axis is a potential target for osteoporosis treatment, which suggests that the SIRT1/FoxO3a contributes to orthopedic diseases [ 41 ]. Consistent with the above research, this article revealed that miR-30b-5p bound to SIRT1 and repressed its expression, and overexpressing miR-30b-5p inactivated SIRT1 and FoxO3a.…”
Section: Discussionmentioning
confidence: 99%
“…Erzhi Pill (EZP), a Chinese Pharmacopeia-listed herbal preparation composed of Ecliptae Herba (Mohanlian, MHL) and Fructus Ligustri Lucidi (Nvzhenzi, NZZ), has been widely applied in the long-term clinical management of post-menopausal symptoms and osteoporosis. 6 In vivo studies have shown that EZP has anti-OP effect on ovariectomized rat model and glucocorticoid-induced osteoporosis (GIOP) rat model, 7 , 8 and shows effects for bone metabolism regulation and alleviation of post-menopausal symptoms in women. 9 , 10 However, due to the complexity of the ingredients of traditional Chinese medicine (TCM) prescription and the limits of existing research methods, its effective constituents, the rationality of herbal combination and the pharmacological mechanisms of promoting bone formation, inhibiting bone absorption and improving bone quality have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that EZP had potential anti-OP effects by preventing the degradation of the alveolar trabecular microarchitecture and alveolar bone loss in ovariectomized rats through activation of the Wnt3a/low-density lipoprotein receptor-related protein 5 (LRP5)/b-catenin signaling pathway (Sun et al, 2014). A study by Liang et al found that EZP played a therapeutic role in an ovariectomized rat model by improving bone metabolism disorder, bone morphology, bone mineral density (BMD) and bone biomechanics and that the underlying mechanism was related to the Sirt1/Foxo signal (Liang et al, 2018). In addition, an in vitro study found that EZP-containing serum could inhibit the proliferation and differentiation of OCs from RAW264.7 cells induced by RANKL (Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%